Causes of changes in basic activities of daily living in older adults with long‐term care needs. (9th September 2020) - Sagari, Akira; Tabira, Takayuki; Maruta, Michio; Miyata, Hironori; Han, Gwanghee; Kawagoe, Masahiro
Abstract: Objective: To elucidate basic activities of daily living (BADL) changes, and the causes, in older adults with long‐term care needs. Methods: This retrospective study utilised long‐term care insurance (LTCI) certification survey data from 2010 to 2017 in City A. Results: In decreasing likelihood of requiring assistance, BADL items were grooming, bathing, getting dressed/undressed, mobility, toilet hygiene, functional mobility and self‐feeding. Cox proportional hazard regression indicated that age correlated with need for assistance for all BADL items. Male sex corresponded to needing assistance with BADL items other than grooming and functional mobility. Shared living corresponded to needing assistance with BADL items other than grooming and bathing. Visual acuity corresponded to needing assistance with grooming. Conclusion: The most significant result was using survival curves to visualise the changes in BADL items of older adults with LTCI. These findings could help develop rehabilitation programs to prevent the need for BADL assistance in older adults.